2011
DOI: 10.1542/peds.2010-1497
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hand, Foot, and Mouth Disease and Herpangina and the Preventive Effect of Hand-washing

Abstract: Hand-washing by preschool-aged children and their caregivers had a significant protective effect against community-acquired HFMD and herpangina from the human enterovirus 71 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 35 publications
2
68
1
4
Order By: Relevance
“…These conditions make it necessary to perform experimental operations related to live HEV71 virus in biosafety level 2 (BSL‐2) facilities,9 an inconvenience, considering the disposal of samples and use of instruments. As an alternative, virus‐like particles (VLPs) are empty particles consisting of viral structural proteins without viral genetic material.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions make it necessary to perform experimental operations related to live HEV71 virus in biosafety level 2 (BSL‐2) facilities,9 an inconvenience, considering the disposal of samples and use of instruments. As an alternative, virus‐like particles (VLPs) are empty particles consisting of viral structural proteins without viral genetic material.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies suggested that early implementation of outbreak management practices can be effective in minimising HFMD spread. 3,7,18,19 There has been no comprehensive systematic review of evidence from HFMD outbreaks, however, to elucidate the most important factors for outbreak control.…”
mentioning
confidence: 99%
“…13,14 Children aged ,5 years are most often affected with transmission occurring via fecal-oral route, vesicle fluid, or respiratory secretions. 15 Coxsackievirus A16 (CVA16) and enterovirus 71 are the 2 most commonly reported causes of HFMD. 16,17 CVA16 has traditionally been considered the most frequent cause of HFMD in the United States.…”
mentioning
confidence: 99%